Dynamic Resonance and Explicit Dialogic Engagement in Mandarin First Language Acquisition. Issue 7 (9th August 2022) - Tantucci, Vittorio; Wang, Aiqing
ABSTRACT: The present article aims to shed light on the relationship between priming and creativity throughout Chinese children's ontogenetic development. It has been suggested that priming in naturalistic interaction occurs not as an exclusively implicit phenomenon. New methodological desiderata beyond traditional acceptability judgments have been proposed, including large-scale corpus-based analysis, as it is noted that priming may correlate with interlocutors' engagement and intersubjectivity. This study is centered on priming occurring creatively, in the form of dynamic resonance, viz. involving the re-elaboration "on the fly" of a previously encountered construction. We fitted a conditional inference tree and mixed effects linear regression based on the normalized entirety of Child-Carer/Child-Peer interaction of the Zhou2 and Zhou3 Mandarin corpora of first language acquisition, from 8 months to 5 years of age. The models indicate that children significantly acquire the ability to creatively reuse a dialogic prime around age 4, distinctively in combination with sentence final particles of intersubjectivity. The latter are non-obligatory markers that speakers employ to express their concern about the addressee's reaction to an ongoing utterance. These results constitute an important discovery in the research on priming, as they indicate that the ability to creatively reuse utterances from others is ontogenetically correlated with explicit dialogic engagement.